2021
DOI: 10.1111/jcpe.13463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different platelet‐rich fibrin matrices for ridge preservation in multiple tooth extractions: A split‐mouth randomized controlled clinical trial

Abstract: Aim To evaluate dimensional changes in the alveolar ridge and bone structure after tooth extraction when L‐PRF or A‐PRF+ was used in comparison to unassisted socket healing. Materials and methods Twenty patients in need of at least three tooth extractions in the aesthetic zone were included. L‐PRF, A‐PRF+ or control was randomly assigned, leaving one empty socket/edentulous site between conditions. CBCT scans were obtained immediately after tooth extraction and after 3 months of healing. Horizontal and vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 57 publications
3
93
0
1
Order By: Relevance
“…Platelet-rich fibrin (PRF), a concentrate of cells and growth factors generated from the centrifugation of whole blood, is one local technique aimed at assisting in alveolar ridge preservation [ 12 , 13 , 14 ], increasing the width of the keratinized mucosa [ 15 ], treatment of periodontal intrabony defects [ 16 ], and treating gingival recessions [ 17 ]. Moreover, PRF is effective in the treatment of ulcers [ 9 ] and is used in other fields such as facial esthetics [ 18 , 19 ] and sports medicine [ 19 ], including meniscal repair [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-rich fibrin (PRF), a concentrate of cells and growth factors generated from the centrifugation of whole blood, is one local technique aimed at assisting in alveolar ridge preservation [ 12 , 13 , 14 ], increasing the width of the keratinized mucosa [ 15 ], treatment of periodontal intrabony defects [ 16 ], and treating gingival recessions [ 17 ]. Moreover, PRF is effective in the treatment of ulcers [ 9 ] and is used in other fields such as facial esthetics [ 18 , 19 ] and sports medicine [ 19 ], including meniscal repair [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The percent socket fill was significantly higher in the PRF group compared to the control group. Castro et al [ 41 ] also demonstrated a significantly higher socket fill after 3 months using CBCT measurement in the PRF treated group compared to the untreated control (Table 5 ).…”
Section: Resultsmentioning
confidence: 82%
“…Most of the included studies evaluated the L-PRF protocol. Additionally, Giudice et al [ 40 ] and Castro et al [ 41 ] evaluated A-PRF + in comparison to L-PRF, Clark et al [ 39 ] evaluated A-PRF and Ustaoglu et al [ 42 ] analyzed T-PRF in comparison to L-PRF. Most of the studies reported solely the used rounds per minutes (rpm) and centrifugation time without referring to the centrifuge design or the applied relative centrifugal force (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations